2017
DOI: 10.1002/bab.1534
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of glycyrrhizin acid and accumulation of endogenous signaling molecule in Glycyrrhiza uralensis Fisch adventitious roots after Saccharomyces cerevisiae and Meyerozyma guilliermondii applications

Abstract: This study reports the best culture conditions for roots growth and accumulation of active components by optimizing the parameters. Glycyrrhiza uralensis adventitious roots metabolites were significantly increased after adding Saccharomyces cerevisiae and Meyerozyma guilliermondii. The highest contents of polysaccharide, glycyrrhizic acid, glycyrrhetinic acid, and total flavonoids were obtained in M. guilliermondii group; the content of glycyrrhizic acid was 5.3-fold higher than the control. In control and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Interestingly, this effect could be partly reversed by B. pumilus G5 inoculation (Figures 1 and 2, Table 2), which is consistent with the previous findings on Trigonella foenum‐graecum (Jasim et al ., 2015) and Cicer arietinum L. (Liu et al . , 2017). We also observed that the beneficial effects of B. pumilus G5 inoculation on the growth and biomass of G. uralensis seedlings were lesser under normal conditions than under drought stress conditions, which may be attributed to that B. pumilus G5 inoculation can greatly improve water status in the continuous process of water loss and rehydration under drought stress condition (Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this effect could be partly reversed by B. pumilus G5 inoculation (Figures 1 and 2, Table 2), which is consistent with the previous findings on Trigonella foenum‐graecum (Jasim et al ., 2015) and Cicer arietinum L. (Liu et al . , 2017). We also observed that the beneficial effects of B. pumilus G5 inoculation on the growth and biomass of G. uralensis seedlings were lesser under normal conditions than under drought stress conditions, which may be attributed to that B. pumilus G5 inoculation can greatly improve water status in the continuous process of water loss and rehydration under drought stress condition (Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus pumilus , a kind of PGB that can be isolated from different plants, alleviated various abiotic stresses in plants (Jha and Subramanian, 2013; Khan and Sirajuddin, 2016; Sirajuddin et al ., 2016). To our knowledge, there are few reports demonstrating the role of PGB in alleviating drought stress in G. uralensis plants (Li et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that this is related to the expressions of some functional genes that are closely associated with the content of bioactive compounds including glycyrrhizic acid and liquiritin in root of licorice species. Some studies [64][65][66] have shown that key functional genes, such as chalcone synthase gene, 3-Hydroxy-3-methylglutary CoA reductase (HMGR) and squalene synthase (SQS), are involved in transcriptional level regulation process in glycyrrhizic acid and liquiritin biosynthesis. Although further studies are required to characterize the expression of functional genes of bioactive compounds, this study provides a theoretical basis for the development of strategies to expand the Glycyrrhiza uralensis cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizin is metabolized to glycyrrhizic acid, a major physiologically active ingredient, by β-D-glucuronidase in vivo [ 26 ]. The carboxyl group in glycyrrhizin is representative of the acidic substances produced by Lactobacillus strains during fermentation in a reduced pH environment [ 27 ]. In our previous study, conversion from liquiritin to liquiritigenin and an increase in glycyrrhizin contents caused by Lactobacillus bacteria was observed in fermented Yijin-tang, a traditional prescription [ 28 ].…”
Section: Discussionmentioning
confidence: 99%